Positive shift in corrole redox potentials leveraged by modest β-CF3-substitution helps achieve efficient photocatalytic C–H bond functionalization by group 13 complexes12. Issue 32 (25th July 2019) - Zhan, Xuan; Yadav, Pinky; Diskin-Posner, Yael; Fridman, Natalia; Sundararajan, Mahesh; Ullah, Zakir; Chen, Qiu-Cheng; Shimon, Linda J. W.; Mahammed, Atif; Churchill, David G.; Baik, Mu-Hyun; Gross, Zeev
Abstract : Tris- and tetrakis-β-trifluoromethylated gallium (3CF3 -Ga, 4CF3 -Ga ) and aluminum (3CF3 -Al, 4CF3 -Al ) corrole systems were synthesized by a facile "one-pot" approach and studied in the context of photocatalytic C–H bond activation. Abstract : Tris- and tetrakis-β-trifluoromethylated gallium (3CF3 -Ga, 4CF3 -Ga ) and aluminum (3CF3 -Al, 4CF3 -Al ) corrole systems were synthesized by a facile "one-pot" approach from the respective tri- and tetra-iodo starting compounds using the FSO2 CF2 CO2 Me reagent. The isolated 5, 10, 15-(tris-pentafluorophenyl)corrole-based compounds set the groundwork for another important β-substituent study in inorganic photocatalysis. As seen previously, –CF3 group substitution leads to red shifts in both the absorption and emission spectra compared to their unsubstituted counterparts (X. Zhan, et al., Inorg. Chem., 2019, 58, 6184–6198). All CF3 -substituted corrole complexes showed strong fluorescence;3CF3 -Al possessed the highest fluorescence quantum yield (0.71) among these compounds. The photocatalytic production of bromophenol by way of these photosensitizing complexes was studied demonstrating that tris-trifluoromethylation is an important substitution class, especially when Ga 3+ is present (experimental TON value in parentheses):3CF3 -Ga (192) >4CF3 -Ga (146) >3CF3 -Al (130) >4CF3 -Al (56) >1-Ga (43) >1-Al (18). The catalytic performance (turn-over number, TON) for benzylbromide formation (from toluene) was found to be:3CF3 -Ga (225) >1-Ga (138) >3CF3 -Al (130) >4CF3 -Ga (126) >1-Al (95) >4CF3 -Al (89); in these trials, benzaldehyde was also detected as a product in which3CF3 -Ga outperforms the other compounds (TON = 109). The tetra-CF3 -substituted4CF3 -Ga and4CF3 -Al species exhibit a dramatic formal positive shift of 116 mV and 126 mV per [CF3 ] group, respectively, compared to the unsubstituted parent species1-Ga and1-Al . However, the absorbance values ( λ abs = 400 nm) of these corrole complexes (all equally concentrated: 4.0 × 10 −6 M) were3CF3 -Al (0.23) >3CF3 -Ga (0.22) >1-Al (0.21) >1-Ga (0.20) >4CF3 -Al (0.19) >4CF3 -Ga (0.15), which helps rationalize why3CF3 -Ga performs the best among these catalysts. These new photosensitizers were carefully characterized by 1 H and 19 F NMR spectroscopy to help verify the number and position (symmetry) of the CF3 groups;3CF3 -Ga and3I-Al were structurally characterized. Distortions in the corrole macrocycle imposed by the multiple β-substitution were quantified.